Probiotics modify tight-junction proteins in an animal model of nonalcoholic fatty liver disease. (July 2016) - Briskey, David; Heritage, Mandy; Jaskowski, Lesley-Anne; Peake, Jonathan; Gobe, Glenda; Subramaniam, V. Nathan; Crawford, Darrell; Campbell, Catherine; Vitetta, Luis
Background: We have investigated the effects of a multispecies probiotic preparation containing a combination of probiotic bacterial genera that included Bifidobacteria, Lactobacilli and a Streptococcus in a mouse model of high-fat diet or obesity-induced liver steatosis. Methods: Three groups of C57B1/6J mice were fed either a standard chow or a high-fat diet for 20 weeks, while a third group was fed a high-fat diet for 10 weeks and then concomitantly administered probiotics for a further 10 weeks. Serum, liver and large bowel samples were collected for analysis. Results: The expression of the tight-junction proteins ZO-1 and ZO-2 was reduced ( p < 0.05) in high-fat diet-fed mice compared to chow-fed mice. Probiotic supplementation helped to maintain tight ZO-1 and ZO-2 expression compared with the high-fat diet group ( p < 0.05), but did not restore ZO-1 or ZO-2 expression compared with chow-fed mice. Mice fed a high-fat diet ± probiotics had significant steatosis development compared with chow-fed mice ( p < 0.05); steatosis was less severe in the probiotics group compared with the high-fat diet group. Hepatic triglyceride concentration was higher in mice fed a high-fat diet ± probiotics compared with the chow group ( p < 0.05), and was lower in the probiotics group compared with the high-fat diet group ( p < 0.05). Compared with chow-fed mice, serum glucose, cholesterol concentration and the activity of alanine transaminase were higher ( p < 0.05), whereas serum triglyceride concentration was lower ( p < 0.05) in mice fed a high-fat diet ± probiotics. Conclusions: Supplementation with a multispecies probiotic formulation helped to maintain tight-junction proteins ZO-1 and ZO-2, and reduced hepatic triglyceride concentration compared with a high-fat diet alone.